1957
DOI: 10.1073/pnas.43.4.305
|View full text |Cite
|
Sign up to set email alerts
|

THE GENETIC CONTROL OF ADENYLOSUCCINASE IN Neurospora Crassa

Abstract: a racemic conglomerate (a mixture of individual d crystals and 1 crystals in equal proportions) such as may result from ordinary nonvital chemical reactions.It is only necessary that the individual crystals be separated far enough from each other so that their solutions do not mix when the crystals dissolve. If the crystals are dissolved under these conditions, each optically active crystal will provide a small amount of an optically active solution.The process might well occur in nature. If a solution of a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

1959
1959
1968
1968

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(21 citation statements)
references
References 6 publications
1
19
0
1
Order By: Relevance
“…STUDIES m micro-organisms (Giles, Partridge and Nelson, 1957;Yura, 1959 Yanofsky andCrawford, 1959) have shown that mutant genes can cause synthesis of altered enzymes, either completely inactive or active at a reduced rate (Fincham, 1957). Differences between allelic mutants may result from the production of enzymes altered to different extents (Giles, Partridge and Nelson, 1957;Yanofsky and Crawford, 1959*;Pateman and Fincham, 1958).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STUDIES m micro-organisms (Giles, Partridge and Nelson, 1957;Yura, 1959 Yanofsky andCrawford, 1959) have shown that mutant genes can cause synthesis of altered enzymes, either completely inactive or active at a reduced rate (Fincham, 1957). Differences between allelic mutants may result from the production of enzymes altered to different extents (Giles, Partridge and Nelson, 1957;Yanofsky and Crawford, 1959*;Pateman and Fincham, 1958).…”
Section: Introductionmentioning
confidence: 99%
“…Differences between allelic mutants may result from the production of enzymes altered to different extents (Giles, Partridge and Nelson, 1957;Yanofsky and Crawford, 1959*;Pateman and Fincham, 1958). In some cases such mutant proteins are strongly affected by environmental conditions, as temperature or ion concentration (Horowitz and Fling, 1953 ;Maasand Davis, 1952).…”
Section: Introductionmentioning
confidence: 99%
“…Almost all amylase mutant genes belong to one locus with the exception of one gene (ae5) according to the results from the present genetic studies. In this point further details of the characterization of these amylase genes have been investigated with the heterocaryon-test for complementation (Giles et al 1957;Woodward et al 1958 <Lacy and Bonner 1961), resulting in restoration of growth on starch.…”
Section: Discussionmentioning
confidence: 99%
“…INTERALLELIc complementation has been observed at loci concerned with purine synthesis in Aspergillus nidulans (Calef, 1956); Xeurospora crassa (Giles, Partridge and Nelson, 1957;Giles, 1958;Ishikawa, 1960;de Serres, 1963); Schizosaccharomyces pombe (Megnet, 1959;Leupold, 1961); Salmonella typhimurium (Gots, Coon and Hild, ig); and Sacc/zaromyces cerevisi& (Bevan and Woods, 1962;Costello and Bevan, 1964;Dorfmann, 1964).…”
Section: Introductionmentioning
confidence: 99%